STUDI KASUS PENANGANAN DIABETES MELLITUS DENGAN SEDUHAN SERBUK KAYU MANIS - Dedy Siska; Yulia Devi Putri; Isna Aglusi Badri; Nurma Zela Gustina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
According to the International Diabetes Federation (IDF) estimated are 463 million adults, 20–79 years, living with diabetes mellitus in 2019 which accounts for 9.3%. Diabetes Mellitus is chronic metabolic disease, characterized by high levels of glucose in the blood. The general objectives this study were describe nursing care for people with Diabetes Mellitus with the problem of unstable blood sugar levels related to the inability of families to care for elderly, and provide Cinnamon Powder Brewed Drinks to decrease blood sugar levels. The method used is case study, namely by collecting data using the format of nursing care. The results from nursing actions carried out for seven days with infusion of cinnamon powder consumed 2 times a day found that patients and families were able to recognize health problems, were able to decide on appropriate actions to treat family members, and to use health facilities. The results of nursing care at Mr. B, there is no dizziness, the vision is no longer blurred. Based on the results of the nursing care carried out, it is hoped that it can be used as learning material and reference material in providing nursing care for Diabetes Mellitus patients.